Comprehensive Meta-Analysis of Functional and Structural Markers of Subclinical Atherosclerosis in Women with Polycystic Ovary Syndrome. (August 2022) - Sun, Dandan; Wu, Yupeng; Ding, Mingyan; Zhu, Fang
The relationship between polycystic ovary syndrome (PCOS) and subclinical atherosclerosis remains unclear. We performed a comprehensive systematic review and meta-analysis to evaluate the effect of PCOS on functional and structural markers of subclinical atherosclerosis as measured by carotid intima-media thickness (cIMT), flow-mediated vasodilation (FMD), nitroglycerin-mediated vasodilation (NMD), pulse wave velocity (PWV), and coronary artery calcium (CAC). Standard mean differences (SMDs) or odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were calculated. Ninety-six articles involving 5550 PCOS patients and 5974 controls were included. Compared with controls, PCOS patients showed significantly thicker cIMT (SMD (95% CI) = .587 (.398, .776), P < .001), lower FMD (SMD (95% CI) = −.649 (−.946, −.353), P < .001) and NMD (SMD (95% CI) = −.502 (−.686, −.317), P < .001), as well as higher PWV (SMD (95% CI) = .382 (.019, .746), P = .039), and increased CAC incidence (OR (95% CI) = 2.204 (1.687, 2.879), P < .001). When analyzing subgroups by age and body mass index (BMI), results were still significant ( P < .05) except for PWV in the BMI subgroup. There was no significant result on sensitivity analysis, and Begg' test or Egger's test. PCOS contributes to subclinical atherosclerosis, resulting in functional and structural changes in cIMT, FMD and NMD, PWV, and CAC incidence.